Pemphigus vulgaris mimicking Steven-Johnson syndrome/toxic epidermal necrolysis: report of an unusual case - Latifah Albrahim; Amal Aboud Alasmari; Majed Aleissa (PAGEPress Publications, 2023)
Pemphigus vulgaris (PV) is an autoimmune blistering disease affecting the skin and mucosa. It clinically presents as painful erosions, mainly in the oral cavity, and flaccid blisters and erosions on the skin. Steven-johnson syndrome/toxic epidermal necrolysis (SJS/TEN) is a severe mucocutaneous drug hypersensitivity reaction characterized by painful, dusky, erythematous eruptions that often progress to blisters, erosions, and extensive epidermal detachment accompanied by systemic symptoms. Herein, we report the case of a 48-year-old man who presented with extensive skin and mucosal lesions following the ingestion of an unknown medication. The patient's symptoms thus clinically mimicked SJS and accordingly, a preliminary diagnosis of SJS was made. Clinical investigation of skin biopsy and direct immunofluorescence assay results, however, indicated PV and a final diagnosis of PV was established.